Current Trends in Alkaloid Research: From Natural Sources to Synthetic Pathways - Shreya Talreja; Dr. Shashank Tiwari (Asian Journal of Pharmaceutical Research and Development, 2024)
Alkaloid is a large family of the diverse natural compounds that are provided with nitrogen atoms. Primarily derived from vegetation, these substances have a great many actions, opening up their applications in medicine, agriculture, and industry. This review is a complete description of alkaloids; starting from the sorting, the biosynthesis, and pharmacological activities, it covers all the aspects. The epitome of their therapeutic uses, such as pain relievers, heart rate stimulants, antimalarial drugs, anticancer drugs, and antibiotics, will be made. The authors present recent frontiers on Biotechnological approaches, the new discovery of alkaloids and the development of environmentally friendly production techniques. This publication is ended with the statement that in the places of personalized medicine, nanotechnology, and synthetic biology, especially alkaloids are key players in creating more effective drugs to different diseases.